The Effect of Problem-Based Learning Model and Blended Learning Model to Metacognitive Awareness as a Reflection Towards a New Normal Era - Kris Yuan; Aftoni Aftoni; Ömer Çobanoğlu (Jurnal Pendidikan Teknologi dan Kejuruan, 2020)
This study aimed to determine differences in the level of metacognitive awareness and learning outcomes of students who learn through problem-based learning model-assisted blended learning on technical drawing material as a reflection towards new normal era education. This study used a test instrument and metacognitive questionnaire with the results of a validity level of 92.58% and the Alpha Cronbach reliability coefficient was categorized as high with a score of 0.876. The research sample was carried out at the state of vocational high school in two classes. Experimental classes learned with a problem-based model were aided by blended learning and a control class learned through a problem-based model. The results showed a significant difference in cognitive domain learning outcomes in the experimental class and metacognitive awareness of students in the two research classes so that this learning model could be used as a reflection in the learning activities of the new normal era.